The Effect of Leadership and Motivation in Measuring Accountability Using the Calibrating Public Accountability Model (CPA Model) - Siti Kustinah; Muhammad Anggionaldi (International Journal of Science and Society, 2021)
The use of school aid funds (BOS) must be accounted for by the beneficiary schools. The performance of a school can be judged by how good the accountability of the school is. The principal plays an important role in realizing accountability in the school he leads. The principal's leadership and motivation are factors that can encourage the achievement of good school accountability. This study aims to determine the effect of leadership and motivation in measuring accountability using the CPA (Calibrating Public Accountability Model) measurement model. The research method used is quantitative verification. The population in this study were all school principals in West Bandung Regency and Cimahi City with the sample technique using a simple random technique. Data collection techniques using questionnaires. Data analysis technique using PLS. The results showed that there was an effect of leadership on accountability, while motivation had no effect on accountability. Simultaneously leadership and motivation affect accountability.